Management of Beyond Center Learning and Circle Time (A Site Study at Early Childhood Education Bunga Bangsa Semarang) - Endang TM, Silviana (2012)
This paper has three objectives. Firstly is to describe students' learning activity in the center at Early Childhood Bunga Bangsa Semarang. Secondly is to describe the teaching activity of teacher in the center at Early Childhood Bunga Bangsa Semarang. And finally, this study aims to describe the classroom setting in the center at Early Childhood Bunga Bangsa Semarang. It is a qualitative research. This study is done at Early Childhood Bunga Bangsa Semarang. The main subject of this research consists of the principal and teachers. Data collection method is using in-depth interview, observation and documentation. Data analysis of this research is using a technique of analyzing data in site. Data validity uses credibility, transferability, confirmability, and dependability. The findings show that (1) students are active in learning in Early Childhood Education Bunga Bangsa Semarang. Students are in group that consists of 10 children and form a circle by singing in environmental scaffolding. On the scaffolding before play, students pray together and greeting with friends and teachers. Students do three learning activities by playing in the centers which are provided by the school. Those activities are (a) play sensory motor such as pouring water in a glass at the cooking center and making a line in the preparation center, as well as watering the plant in the nature center, (b) do a role play such as acting as a doctor in the role play center, and (c) development play by creating a picture in the art center and arranging the block in the development center. In the scaffolding after playing, students do a recall activity to remember the learning experience gained from the games or provided in the beyond center. (2) Teaching activities of teachers in Early Childhood Education Bunga Bangsa Semarang is done by considering the theme and also using principles of learning by learning. Teachers prepare all the necessary administration such as preparing APE. The teachers make an agreement to the students and create a fun atmosphere such as doing the physical exercise activity. Material is delivered by giving question and answer and also demonstration in the center used, the activity of students are recorded everyday in a daily report. To reinforce the learning experience of students, teachers have a review in the end of learning. (3) Classroom setting in the Early Childhood Education Bunga Bangsa Semarang considers the comfort and students' needs. The classroom is created in an interesting decoration by installing various ornaments such as poster and students' work. The class is handled by two teachers that consist of a main teacher and a teacher assistant. Those teachers make the moving class system from one center to another center in Early Childhood Education Bunga Bangsa Semarang run effectively. Formation of the seat is made in the form of a circle where students sit and listen to the teacher's explanations in carpet.